A miniaturized microbial fuel cell with three-dimensional graphene macroporous scaffold anode demonstrating a record power density of over 10 000 W m−3 1. Issue 6 (25th January 2016) - Ren, Hao; Tian, He; Gardner, Cameron L.; Ren, Tian-Ling; Chae, Junseok
Abstract : We report a miniaturized microbial fuel cell, integrated with a 3D free-standing graphene scaffold, delivering a record high power density of 11 220 W m −3 . Abstract : A microbial fuel cell (MFC) is a bio-inspired renewable energy converter which directly converts biomass into electricity. This is accomplished via the unique extracellular electron transfer (EET) of a specific species of microbe called the exoelectrogen. Many studies have attempted to improve the power density of MFCs, yet the reported power density is still nearly two orders of magnitude lower than other power sources/converters. Such a low performance can primarily be attributed to two bottlenecks: (i) ineffective electron transfer from microbes located far from the anode and (ii) an insufficient buffer supply to the biofilm. This work takes a novel approach to mitigate these two bottlenecks by integrating a three-dimensional (3D) macroporous graphene scaffold anode in a miniaturized MFC. This implementation has delivered the highest power density reported to date in all MFCs of over 10 000 W m −3 . The miniaturized configuration offers a high surface area to volume ratio and improved mass transfer of biomass and buffers. The 3D graphene macroporous scaffold warrants investigation due to its high specific surface area, high porosity, and excellent conductivity and biocompatibility which facilitates EET and alleviates acidification in the biofilm. Consequently, the 3D scaffold houses an extremely thick and dense biofilm from the Geobacter -enriched culture, delivering an areal/volumetric current density of 15.51 A m −2 /31 040 A m −3 and a power density of 5.61 W m −2 /11 220 W m −3, a 3.3 fold increase when compared to its planar two-dimensional (2D) control counterparts.